Blood salvage with a continuous autotransfusion system compared with a haemofiltration system. - Nitescu N; Bengtsson A; Bengtson JP (Perfusion, 2002)
BACKGROUND: Red blood cells may be destroyed by autotransfusion processing during intraoperative salvage. The aim of the present study was to evaluate the blood component recovery rate of techniques built on either continuous centrifugation and washing, or haemofiltration (HF). METHODS: Two different methods used in blood salvage - red cell salvage with continuous processing with centrifugation and saline washing (Continuous Auto Transfusion System, CATS) and whole blood recirculation through a 30000-Da filter, i.e., HF - were compared in a randomized laboratory study using donor whole blood activated by cobra venom factor. The recovery of red blood cells, haemoglobin, free haemoglobin, leucocytes, platelets, albumin, total protein and potassium was measured. RESULTS: The recovery of red cells was 86% with CATS and 76% with HF. HF had a significantly higher recovery of leucocytes (CATS 20%, HF 63%), platelets (CATS 4%, HF 37%), albumin (CATS 0.2%, HF 70%), total protein (CATS 1.3%, HF 71%) and potassium (CATS 2%, HF 17%). Less than 1% haemolysis was obtained in processed blood from both groups. CONCLUSION: Both methods caused little destruction of the red blood cells during processing. There was a larger reinfusion of leucocytes, platelets, albumin, total protein and extracellular potassium when HF was used compared with the 'CATS' method.